2019
DOI: 10.3389/fnana.2019.00048
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Amphetamine and Methamphetamine on the Release of Norepinephrine, Dopamine and Acetylcholine From the Brainstem Reticular Formation

Abstract: Amphetamine (AMPH) and methamphetamine (METH) are widely abused psychostimulants, which produce a variety of psychomotor, autonomic and neurotoxic effects. The behavioral and neurotoxic effects of both compounds (from now on defined as AMPHs) stem from a fair molecular and anatomical specificity for catecholamine-containing neurons, which are placed in the brainstem reticular formation (RF). In fact, the structural cross-affinity joined with the presence of shared molecular targets between AMPHs and catecholam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 250 publications
(336 reference statements)
0
54
0
Order By: Relevance
“…Thus, although amphetamine elicits the non-physiological release of dopamine by reversal of dopamine transporter from cells lacking VMAT2, it is likely that sensitization of output areas plays a greater role in explaining the response. Additionally, given the sites of KO cells including the LC, the behavioral output seen here likely stems from effects exerted by other signaling systems, notably that of noradrenaline signaling, which has considerable interactions with dopaminergic signaling with relevance to the response to stimulants (Ferrucci et al, 2019 ), and has been implicated in sensitivity to stereotypies (Weinshenker et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although amphetamine elicits the non-physiological release of dopamine by reversal of dopamine transporter from cells lacking VMAT2, it is likely that sensitization of output areas plays a greater role in explaining the response. Additionally, given the sites of KO cells including the LC, the behavioral output seen here likely stems from effects exerted by other signaling systems, notably that of noradrenaline signaling, which has considerable interactions with dopaminergic signaling with relevance to the response to stimulants (Ferrucci et al, 2019 ), and has been implicated in sensitivity to stereotypies (Weinshenker et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…For many of the parameters studied, crosstalk on molecular and cellular levels between the different monoamine systems exist—for instance, locomotor response to cocaine has been suggested to be exaggerated due to potentiation of the 5HT1A receptor (Szumlinski et al, 2004 ), and indeed diverging results were found depending on the involvement of one or several monoamine systems (Isingrini et al, 2016b ). At the network level, the transmission of neurotransmitters has cross-modulatory effects, such as described for dopamine and noradrenaline (Smith and Greene, 2012 ; Ferrucci et al, 2019 ). Considering the above-mentioned limitations of the present study, pharmacological interventions or the site-specific introduction of shRNA targeting Vmat2 in adult Calb2-Cre mice may clarify the involvement of each region and corresponding transmitter system, as well as avoid developmental effects of a constitutive knockout.…”
Section: Discussionmentioning
confidence: 99%
“…This is evident by a variety of behavioral effects produced by psychostimulants based on autophagy-dependent alterations (56,61). Psychostimulants alter neuroplasticity of DA and NE neurons through receptor sensitization/desensitization while affecting their activity and metabolism (7,49). In keeping with this, autophagy orchestrates the turnover and responsivity of various neurotransmitter receptors by intermingling with the proteasome system and intracellular trafficking and secretory pathways (66,67).…”
Section: A Brief View Of the Autophagy Machinery: From Degradation Ofmentioning
confidence: 99%
“…NE-LC and DA-VTA neurons are readily activated by stressful events involving neural processes related to perception, cognitive evaluation, appraisal, and stressdependent hormonal factors. These systems operate in parallel and in synergism, allowing to implement neural adaptations and behavioral strategies aimed at supporting resilience and overcoming stressful events (6)(7)(8)(9). In fact, both systems are crucially involved in reward and in efforts to support motivation and coping (3,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, all DMRs of the genomic DNA methylation chip data in the pairwise comparisons of the three groups were included in the KEGG pathway analysis, which showed that seven specific pathways were statistically significant. Moreover, all seven pathways, including the Circadian entrainment (23), Cholinergic synapse (24), Glutamatergic synapse (25), Retrograde endocannabinoid signaling (26), GABAergic synapse (27), Morphine addiction (28), and PI3K-Akt signaling pathways (29), were identified to be associated with MA addiction or reward circuits.…”
Section: Analysis Of Dmr Data Inferred the Role Of The Circadian Entrmentioning
confidence: 99%